Fluoride adsorption from aqueous solution using activated carbon obtained from KOH-treated jamun (Syzygium cumini) seed. Issue 6 (December 2017) - Araga, Ramya; Soni, Shantanu; Sharma, Chandra S.
Graphical abstract: Highlights: Jamun seed derived activated carbon was synthesized by using KOH as activating agent. Surface hydroxyl groups of prepared activated carbon participated in the fluoride adsorption. Adsorption capacity was found to be greater than the other biomass derived activated carbons. Fluoride content of groundwater samples as treated with adsorbent was reduced to the WHO permissible limit. Abstract: In this study, for the first time, jamun seed derived activated carbon was used as an adsorbent for removal of fluoride from water. Activated carbon was prepared by KOH activation of jamun seed and subsequent pyrolysis at 900 °C. The fluoride sorption experiments were carried out under batch mode to optimize the various influencing parameters such as contact time (0–3 h), dosage of adsorbent (20–500 mg), initial fluoride concentration (2–20 mg L −1 ), temperature (298–308–318 K), and pH (2.5–10). The contact time and pH for maximum fluoride uptake were observed at 120 min and 2.5 respectively. Maximum adsorption capacity (3.65 mg g-1) of fluoride on activated carbon was found for 10 mg L −1 of initial fluoride concentration using 0.4 g L −1 adsorbent dosage. The equilibrium data were found to follow Dubinin-Radushkevich isotherm among the three applied isotherm models (Freundlich, Temkin, and Dubinin-Radushkevich) and pseudo-second-order kinetic mechanism with the rate constant of 0.036 g mg −1  min −1 . Thermodynamic analysis revealed that the adsorption process was exothermic in nature. Performance of the prepared adsorbent was compared with other reported biomass derived activated carbons and it was observed that the proposed adsorbent is efficient in terms of its adsorption capacity. In addition to synthetic samples, field water samples collected from fluoride affected villages were also tested for adsorption experiments.